Arte em Cena: teatro na escola pública como prática de liberdade - Oliveira, Marcia Cristina Polacchini de (2014)
The present work discusses the Art on Stage Project, its creational and development process, held at the State School Plínio Barreto in São Paulo county, and also includes the analisys of the projects student theater company (2007-2014), a teen s group that holds the same name, and evaluates its creative process, assemblies and performances that took place at school and beyond. This research assumes that the theater concept is a practice of freedom and a possibility to provide the opportunity for public schools students and alumni to expand their ability to create as well as to be part of a constructive process, and also assumes theather as a facilitator of their potentialities development in today's society, with an more human and active participation. I take the premise that art - theater - constitutes a critical and transformative educational activity, and I use Edgard Morin, Paulo Freire, and Lev Vigotski thoughts, in a historical and cultural perspective, as well as theatricals Constantin Stanislavski and Augusto Boal theories and practices, to promote a qualitative approach investigation assumed as action research, that includes the direct participation of the students involved in the process. This work developed a methodology which reframed action research due to a critical-dialogical and participatory process that understands that students can become empowering agents and art and culture producers.